Provision of assistive technology devices among people with ALS in Germany: a platform-case management approach. Issue 5 (3rd July 2018) - Funke, Andreas; Spittel, Susanne; Grehl, Torsten; Grosskreutz, Julian; Kettemann, Dagmar; Petri, Susanne; Weyen, Ute; Weydt, Patrick; Dorst, Johannes; Ludolph, Albert C.; Baum, Petra; Oberstadt, Moritz; et al.
Abstract: Objective : The procurement of assistive technology devices (ATD) is an essential component of managed care in ALS. The objective was to analyze the standards of care for ATD and to identify challenges in the provision process. Methods : A cohort study design was used. We investigated the provision of 11, 364 ATD in 1494 patients with ALS at 12 ALS centers in Germany over four years. Participants were patients that entered a case management program for ATD including systematic assessment of ATD on a digital management platform. Results : Wheelchairs (requested in 65% of patients), orthoses (52%), bathroom adaptations (49%), and communication devices (46%) were the most needed ATD. There was a wide range in the number of indicated ATD per patient: 1 to 4 ATD per patient in 45% of patients, 5 to 20 ATD in 48%, and >20 ATD in 7% of patients. Seventy percent of all requested ATD were effectively delivered. However, an alarming failure rate during procurement was found in ATD that are crucial for ALS patients such as powered wheelchairs (52%), communication devices (39%), or orthoses (21%). Leading causes for not providing ATD were the refusal by health insurances, the decision by patients, and the death of the patient before delivery of the device. Conclusions : The need for ATD was highly prevalent among ALS patients. Failed or protracted provision posed substantial barriers to ATD procurement. Targeted national strategies and the incorporation of ATD indication criteria in international ALS treatment guidelines are urgently needed to overcome these barriers.